Supply Chain Management Practices and Organizational Performance: An Investigation from Service Industry - Inda Sukati; Shouvik Sanyal; Ali Mohsin Ba Awaain (International Journal of Supply Chain Management, 2020)
ABSTRACT This objective this study was to evaluate how SCM practices dimension (SC partnerships, company relationships with customers, information sharing in supply chains, information technology, employee training and company internal operations) are related to the performance of business organizations in the tourism service industry. The target respondents in this study were tourism service provider (hotel, restaurant and transportation company). There were four hypotheses that have been tested on this research. Hypothesis (H1), the standard path coefficient between the strategic SC partnership and organizational performance was .56 and is significant at the level of .001. Thus, H1 was supported. Hypothesis (H2), the standard path coefficient between customer relations and organizational performance was .15 and was significant at the .001 level. Therefore, H2 was supported. Hypothesis (H3) examines the effect of information sharing and organizational performance. The standardized path coefficient between information sharing and organizational performance was .52 and was significant at the .001 level. Thus, H3 is supported. Hypothesis (H4), the standard path coefficient between information technology and organizational performance is .62 and was significant at the level of .001. Therefore, H4 was also supported. Hypothesis (H5) examines the effect of internal operations and organizational performance. The standardized path coefficient between internal operations and organizational performance was .42 and was significant at the .001 level. Thus, H5 is supported. Keywords: Supply chain management practices, organizational performance.